Effect of Rosiglitazone on Coronary Angiogenesis in Diabetic and Control Rats - Ensieh Salehi; Majid Khazaei; Bahman Rashidi; Shaghayegh Haghjooye Javanmard (مجله دانشکده پزشکی اصفهان, 2011)
Background: Peroxisome proliferator–activated receptors (PPARs) are ligand-activated transcription factors of nuclear receptor superfamily, consisting of three subtypes: PPARα, γ, β/δ. Clinical evidence suggests that PPARs may be involved in regulating angiogenesis. In this study, we examined the hypothesis that whether activation of PPARγ by Rosiglitazone, a PPARγ agonist, can alter coronary angiogenesis in diabetic and control rats. Methods: Twenty four male rats were randomly divided into four groups as follows: group 1: control rats received vehicle; group 2: control rats received Rosiglitazone (8mg/kg/day) by gavage every day; group 3: diabetic rats received vehicle; group 4: diabetic rats received Rosiglitazone (8mg/kg/day) by gavage everyday. All rats were sacrified after 21 days and their hearts muscles were harvested for immonohistochemistry. Finding: The mean capillary density in control rats was higher than diabetic rats (P = 0.08). Rosiglitazone treatment could not change capillary density of the heart in diabetic rats (121.71 ± 13.32 versus 136.62 ± 7.02/mm2) and nondiabetic rats (153.78 ± 11.08 versus 135.96 ± 4.3/mm2). Conclusion: Our findings demonstrate that diabetes is associated with reduced capillary density in the heart and PPARγ activation by Rosiglitazone could not alter angiogenesis in diabetic and non-diabetic rats.